Pengaruh Terpaan Iklan Layanan Masyarakat "Vaksinasi Melatih Tubuh Kenal, Lawan Dan Kebal" Di Televisi Terhadap Sikap Masyarakat (Survei Pada Warga Kelurahan Pisangan, Tangerang Selatan) - Sherina Riznufirdine Alfariz, (2021)
Since the outbreak of the Covid-19 virus which first appeared in 2019 in Wuhan China, cases of Covid-19 in Indonesia as of March 12, 2021, the positive number of Covid-19 reached 1,386,556. One of the government's efforts to overcome the COVID-19 pandemic, is to provide a COVID-19 vaccine which functions to encourage the formation of specific immunity in COVID-19 to avoid contracting or possibly becoming seriously ill caused by the Covid-19 Virus. However, there are still many people who doubt the safety of the covid-19 vaccine and doubt the usefulness of the covid-19 vaccine. So the KPCPEN agency issued a public service advertisement "Training The Body To Know, Fight, Immune" to educate the public about vaccines and encourage people to get vaccines. The purpose of this study was to determine and measure the effect of exposure to public service advertisements "Training The Body To Know, Fight, Immune" on television on public attitudes. The research method used was quantitative explanative. This study uses Hierarchy effect models, which assume that humans learn something first from advertising, then feel emotional behavior about the products in the advertisement, and finally take action. The survey was conducted by sending a questionnaire to 100 respondents from the Pisangan village community. The result of the calculation of the correlation test states that advertisement exposure (x) and public attitudes (y) have a moderate correlation level of 0.474. Based on the results of the simple linear regression test, the independent variable (x) has a positive effect on the dependent variable (y) when manipulated. From the results of the detemination coefficient test, the level of influence or contribution of advertising exposure (x) to public attitudes (y) was 22.4% and the rest was influenced by other factors. Based on the results of the hypothesis test or t-test, the t-value is based on the t-count of 5.364> 1.660 t-table, then Ha is accepted and Ho is rejected. Thus, there is an influence between exposure to public service advertisements "Vaccination to Train a Familiar, Opposing, and Immune Body" on television on public attitudes. Keywords: covid-19, covid-19 vaccine, public service advertisements, public attitudes, Hierarchy effect models